Lecithin Alleviates Memory Deficits and Muscle Attenuation in Chinese Older Adults and SAMP8 Mice - Wang, Xianyun; Li, Dajun; Li, Xiao Ying; Lu, Weizhao; Ding, Huini; Qi, Chengyan; Wang, Xuan; Shen, Jing; Chi, Yafei; Li, Tiantian; Dunk, Michelle M.; An, Yu; et al. (Advanced science, 2025)
Identifying the mechanistic targets of crosstalk between sarcopenia (SA) and mild cognitive impairment (MCI) is critical for screening high‐risk populations and exploring effective prevention and treatment strategies. In a nationwide multicenter prospective cohort study combined with an RCT study, it is found that indexes of muscle health reveal a strong predictive relationship with cognitive performance assessed using the Montreal Cognitive Assessment (MoCA). Furthermore, Random Forest models suggest that lecithin can predict both diseases. Erythrocyte lipid analysis and RCT study indicate the protective function of lecithin and the potential involvement of irisin in that process. In rodent models, phosphocholine (PC) alleviates learning and memory impairments and muscle attenuation in SAMP8 mice, while FNDC5/irisin knockdown accelerates brain and muscle damage or eliminates the protective effects of PC. Transcriptome analysis shows that PGC1α (the regulator of FNDC5) is regulated by PC treatment, and the results of knocking out PGC1α and FNDC5/irisin are consistent. Here it is found that muscle‐secreted FNDC5/irisin is a key target of “muscle‐brain” crosstalk, and lecithin may postpone the progression of MCI and SA by stimulating PGC1α‐FNDC5/irisin‐mediated cross‐protection of cognition and skeletal muscle. This study opens a new avenue for safeguarding cognition and muscle health, averting disability in older age, and treating age‐related pathologies through lecithin supplementation. It serves as a promising nonpharmacological intervention for the crosstalk of muscle and cognition. The protective effects of lecithin demonstrate in the investigations of both humans and mice provide strong support for the development of PC interventions.